Pemenuhan Kebutuhan Oksigenasi Pasien Asthma Bronchiale dengan Teknik Relaksasi Batuk Efektif - Nurleli Nurleli; Ainayya Afninda Utami; Erita Gustina; Suvi Novida (Jurnal Riset Hesti Medan, 2021)
Bronchial asthma is a disease of respiratory tract obstruction caused by muscle contraction, inflammation, and accumulation of secretions around the bronchi. Meeting the need for oxygenation is part of the management of asthmatic bronchial patients. This case study aims to describe the fulfillment of oxygenation needs. The case study method uses a descriptive design with a nursing care approach in the same two cases, namely respondents with bronchial asthma. The case study was conducted at the Putri Hijau Kindergarten II Hospital from October to December 2018. The data collection method was through interviews, physical examinations, supporting examinations, using the assessment format as an instrument in data collection. After intervention with effective cough relaxation techniques as well as collaboration in the administration of drug and oxygen therapy, during four days of treatment, both respondents were able to meet their oxygenation needs optimally. It was concluded that the intervention had an effect on the effectiveness of airway clearance so as to eliminate shortness of breath, based on this study, it is hoped that it can be applied by health workforce.